Sandra Eleta - the invisible world - Kupfer, Mónica E. (Editorial RM, 2018)
Following her recent inclusion in the Hammer's Radical Women exhibition, the relatively little-known career of Panamanian photographer Sandra Eleta (born 1942) is documented in this first full monograph. Her work covers more than four decades and focuses mainly on an approach to the daily life of the Afro-American and indigenous peoples of the Atlantic region of the Republic of Panama. The present is the first complete monograph of her work and it includes her influential work "Portobelo, Photography of Panama", a photographic and anthropological essay about life in Portobelo. The book also contains revealing personal writings, a must read to understand the universe of this creator
Keywords: Eleta, Sandra -- 1942-; Eleta, Sandra; Portrait photography; Photography, Artistic; Panamanians / Panama / Portobelo / Portraits; Portobelo (Panama) / Pictorial works; Panamanians; Photographers; Panama; Panama / Portobelo; Biography; Portraits; Bildband